A szerződési szabadság gazdaságszabályozó szerepe - Török, Éva (Debreceni Jogi Műhely, 2014)
The freedom of contract has an economic regulating rule, both on individual and on communal level; secures either the enforcement of the law of the self-determination of the parts, or the possibility of market participation. Gwartney and Lawson, elaborators of the conception of the economic freedom, said that the capstones of the economic freedom are the freedom for the decisions and for the acts of the persons, moreover the volunteering of the exchange, the freedom of the competition, the protection of the persons and their properties. Several indicators are available for measuring the economic freedom. One of them is the index of the Canadian Fraser Institute Economic Freedom of the World; furthermore it is one of the most respected indicators. This index investigates the rate of the economic freedom by using 42 factors grouped to five parts. These five components are the legal system and the protection of the ownership, size of the state, reliable, so stable valued money, the freedom of the foreign trade, the capital market and the regulation of the business. The last four items can be identified as the freedom of the contract.